Exploring how stay-at-home orders during the COVID-19 pandemic impedes engagement along the HIV/AIDS care continuum in public hospitals of Southwest Ethiopia: a qualitative study - Gizaw, Abraham Tamirat; Abayneh, Mengistu (Frontiers in Public Health, 2024)
Introduction: COVID-19 has spread rapidly around the world. Immediately after the first confirmed case of COVID-19 in Ethiopia in March 2020, the government of Ethiopia took several measures.Purpose: This study aimed to explore how stay-at-home orders during the COVID-19 pandemic impedes engagement along with HIV/AIDS care in public hospitals of Southwest Ethiopia. Additionally, we aimed to explore the psychosocial challenges to get the service during stay-home order.Methods: A descriptive qualitative study was conducted using semi-structured, in-depth interviews from May 20 to June 3, 2020. Twenty-seven study participants were recruited from purposively selected people living with HIV/AIDS (PLWHA) who had delayed, declined, or discontinued after COVID-19 had been confirmed in Ethiopia (March 13, 2020). The participants were engaged in phone interviews and audio-recorded. Data were audio-recorded, transcribed verbatim, translated, and analyzed using inductive thematic analysis in Atlas ti.7.1 software package.The main themes and sub-themes identified were psychosocial issues (such as depression, hopelessness, and fear), risk perception (including high risk, susceptibility, and severity), forceful enforcement of stay-at-home orders (such as police beating, community leaders disgracing, and influence from families and relatives), socioeconomic factors (such as stigma, religion, and transportation costs), misinformation about COVID-19 (such as lockdowns and ART stock-outs), and health care factors (such as inadequate health information and long distances to health facilities).Overall, these findings were similar to the challenges experienced by PLWHA in adhering to the recommended continuum of care. However, there are additional factors due to COVID-19 like misinformation and forceful stay-home-order implementation impeded the continuum of care. Therefore, strengthening information, education, and communication is particularly important.